REAL STATE MEDIATION: CHALLENGES AND PERSPECTIVES - Francisco Gorjón-Gómez (Revista do Direito)
We present to the MSC community a first approach to the scope of real estate mediation, with an emphasis on real estate arbitration, where we observe the various areas of opportunity that arise in this area of ​​conflict resolution methods, and how they impact a sector of broad economic influence and great social resonance. We also observe the feasibility of managing real estate conflicts, where their constituent elements, characteristics and regulatory frameworks make them equally prone to the adoption of measurement and arbitration as self-composition formulas, as if it were commercial, family or criminal mediation, or even more so, consolidated sectors, due to their broad local, national and international support.